AI Opportunities for Emerging Businesses in Libya: Navigating Challenges for Success (The International Journal of Engineering & Information Technology (IJEIT), 2024)
This research paper aims to investigate the potential contributions of Artificial Intelligence (AI) in fostering business development in emerging businesses within the Libyan context. By proposing various AI models and exploring their applications, this study seeks to provide insights into how AI can positively impact different aspects of business operations and strategies. For data collection and analysis, experts were selected to participate in this study to ensure a comprehensive understanding of how AI can positively impact different types of businesses in Libya. The primary data was collected through a combination of questionnaire and semi-structured interviews. The paper present a comprehensive analysis of the opportunities and challenges associated with AI adoption in Libya's emerging business sector, offering recommendations for leveraging AI technologies to enhance competitiveness, productivity, and innovation. This study contributes valuable insights to the literature on AI adoption in emerging business environments, offering a comprehensive analysis of the opportunities and challenges in Libya's emerging business landscape